Correlation of Overexpression of PDL-1 With Lymph Node Metastasis in Penile Carcinoma - Ni Putu Diah Witari; Analysa Analysa; Putu Oki Lestari (http://dharmais.co.id/, 2026)
Background: Penile cancer cases are rarely found, but in the Bali area, the case is higher than in other regions in Indonesia. The death rate of penile cancer is still high, and 80% of cancer deaths are related to metastasis. As immunotherapy in cancer develops, PDL-1 is becoming one of the targets for immune therapies that promise to replace conventional therapies or serve as adjunct therapies. This study aims to see the correlation between the overexpression of PDL-1 and lymph node metastasis, which is one indicator of the poor prognosis of a cancer.Methods: This study used a case-control study design with a retrospective approach. The sample was 70 primary squamous type penile cancer formalin-fixed paraffin-embedded (FFPE) specimens with complete clinical data from several Anatomic Pathology laboratories in Bali, 2015-2023. FFPE sections that were damaged and did not have complete data were excluded. The case is 35 with lymph node metastasis, and 35 without lymph node metastasis as a control. In this study, the correlation between PDL-1 overexpression and tumor grading and lymph node metastasis in penile carcinoma will be explored. Data analysis with Chi-square using SPSS. The p-value for the significance test was less than 0.05. The accuracy of the data is determined by a 95% confidence interval (CI). The research was conducted from February 2024 to August 2024 Results: This study showed a significant correlation between PDL-1 overexpression and lymph node metastasis, p < 0.05. There was a significant correlation of PDL-1 overexpression with lymph node metastasis (p = 0.001). There was a correlation between overexpression of PDL-1 and tumor size (p = 0.035), tumor grading (p = 0.027), and lymphatic invasion (p = 0.038). There was no correlation between PDL-1 overexpression with age (P = 0.424)Conclusions: This study demonstrates a significant correlation between PDL-1 overexpression and lymph node metastasis in penile carcinoma patients. Furthermore, PDL-1 overexpression is significantly associated with larger tumor size, higher tumor grade, and lymphatic invasion. These results suggest that PDL-1 serves as a critical prognostic biomarker for predicting disease aggressiveness and metastatic potential.